CHARACTERIZATION AND DETECTION OF NORMAL LIVER TEXTURE USING ULTRASOUND - Mustafa, Ashraf; Gar Elnabi, Mohamad Elfadil Mohamed; Ahmed, Mona; Sulieman, Abdelmoneim (International Journal of Research -GRANTHAALAYAH, 2018)
The main research conducted to know the importance of duplex Ultrasonography in the control, follow-up & the diagnosis of the different types of liver post-transplantation problems. Three hundred normal liver Doppler scan done to be as a reference (liver span and echotexure by the naked eye; not by image processing programme - IPP; in young expected normal patients in relation to normal liver transplanted patients- not a diseased liver, cirrhosis or hepatitis) to the Sudanese normal livers before starting the research, and about 65 Sudanese patients found with liver transplantations from them only 45 were available for liver Doppler scan. The data had been collected from the 300 normal objects population are the students of faculty of medicine in Al Rabat University (ages between 16-22 yrs., 48 % M; 52% F); the study done during the period from 1st April 2016 to 30th July 2017. The liver span is in the range (9.5-13.9 cm), the majority is of homogenous echo - level grading. The Statistical Package for Social Science – SPSS version 20.0 is used; no significant difference found between young males and females, however, that the upper limit of the liver span is a little bit more than the international values.